The Development of Sea-Wave Power Plant Model as Maritime-Based Science Instructional Media for Junior High School Students in Coastal-Areas - Zulirfan, Zulirfan; Rahmad, M; Yennita, Yennita; Sudrajat, Hendar (Proceedings of the UR International Conference on Educational Sciences, 2018)
In order for science learning to be interesting and beneficial for students, science instructions must be oriented to the students daily environment. One way to link science instruction with the surrounding environment is by showing the application of scientific concepts to the appropriate technology. For students who live and study in coastal areas, the application of the concept of science should be linked to the sea that they observe every day. In this study a set of science learning media has been developed in the form of sea-wave power plant model. This model is designed so that it can visualize the process of using sea waves to produce electrical energy in the small scale. Expert assessment shows that the model of sea-wave power plant is declared valid so, it is suitable to be used as an instructional media for junior high school in science learning.